DIVERSITY OF GASTROPODS IN MANGROVE ECOSYSTEM OF POTON BAKO HAMLET, JEROWARU DISTRICT, EAST LOMBOK REGENCY, NTB - Ahmad, Wira Nata Kusumah; Larasati, Chandrika Eka; Damayanti, Ayu Adhita (Jurnal Perikanan Unram, 2024)
This study aims to determine the composition of Gastropoda species and the index of diversity, seregation and dominance in mangrove ecosystems in Poton Bako Hamlet. Sampling was carried out at 2 different stations using line and square transects and included Gastropod collection as well as supporting parameter data such as temperature, salinity, pH and substrate carried out directly. Based on the composition of the abundance of Gastropod species obtained 13 Families, 21 Genuses, 32 species. Producing a total number of biota obtained 606 individuals spread across Station 1 as many as 289 ind and Station 2 as much as 319 ind. The type of Terebralia sulcata is most commonly found at each station. The results of this study describe the ecological conditions at Station 1 with a diversity index (H = 2.23) classified as medium, a uniformity index (E = 0.72) classified as high and a dominance index (D = 0.15) classified as low. While the ecological condition at Station 2 with a diversity index (H'=1.44) is moderate, the uniformity index (E= 3.94) is high and the dominance index (D= 0.46) is high.